Spindles are highly heritable as identified by different spindle detectors. Issue 4 (9th November 2020) - Goldschmied, Jennifer R; Lacourse, Karine; Maislin, Greg; Delfrate, Jacques; Gehrman, Philip; Pack, Frances M; Staley, Bethany; Pack, Allan I; Younes, Magdy; Kuna, Samuel T; Warby, Simon C
Abstract: Study Objectives: Sleep spindles, a defining feature of stage N2 sleep, are maximal at central electrodes and are found in the frequency range of the electroencephalogram (EEG) (sigma 11–16 Hz) that is known to be heritable. However, relatively little is known about the heritability of spindles. Two recent studies investigating the heritability of spindles reported moderate heritability, but with conflicting results depending on scalp location and spindle type. The present study aimed to definitively assess the heritability of sleep spindle characteristics. Methods: We utilized the polysomnography data of 58 monozygotic and 40 dizygotic same-sex twin pairs to identify heritable characteristics of spindles at C3/C4 in stage N2 sleep including density, duration, peak-to-peak amplitude, and oscillation frequency. We implemented and tested a variety of spindle detection algorithms and used two complementary methods of estimating trait heritability. Results: We found robust evidence to support strong heritability of spindles regardless of detector method ( h 2 > 0.8). However not all spindle characteristics were equally heritable, and each spindle detection method produced a different pattern of results. Conclusions: The sleep spindle in stage N2 sleep is highly heritable, but the heritability differs for individual spindle characteristics and depends on the spindle detector used for analysis.